(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article offers a first look at a key institution in the taxation during the colonial period: The Cajas Reales. The Royal Cash Box in Valladolid is a forgotten institution for the historiography from Michoacan, and although studies have been conducted on the Intendancy of Valladolid and the Bourbon reforms, not enough interest has been paid to this tax short-lived but important institution over the last decades of colonial Michoacán. The aim of this paper is to show when and how it was founded, its officers, their powers and the conflicts triggered by various institutions and authorities from Michoacán.